Selenium protects the immature rat heart against ischemia/reperfusion injury - Ostadalova, Ivana; Vobecky, Miloslav; Chvojkova, Zuzana; Mikova, Dana; Hampl, Vaclav; Wilhelm, Jiri; Ostadal, Bohuslav (Molecular and cellular biochemistry, 2007)
The aim of the study was to find out whether administration of selenium (Se) will protect the immature heart against ischemia/reperfusion.The control pregnant rats were fed laboratory diet (0.237 mg Se/kg diet); experimental rats received 2 ppm Na(2)SeO(3) in the drinking water from the first day of pregnancy until day 10 post partum. The concentration of Se in the serum and heart tissue was determined by activation analysis, the serum concentration of NO by chemiluminescence, cardiac concentration of lipofuscin-like pigment by fluorescence analysis. The 10 day-old hearts were perfused (Langendorff); recovery of developed force (DF) was measured after 40 min of global ischemia. In acute experiments, 10 day-old hearts were perfused with selenium (75 nmol/l) before or after global ischemia. Sensitivity to isoproterenol (ISO, pD(50)) was assessed as a response of DF to increasing cumulative dose.Se supplementation elevated serum concentration of Se by 16%. Se increased ischemic tolerance (recovery of DF, 32.28 +/- 2.37 vs. 41.82 +/- 2.91%, P < 0.05). Similar results were obtained after acute administration of Se during post-ischemic reperfusion (32.28 +/- 2.37 vs. 49.73 +/- 4.40%, P < 0.01). The pre-ischemic treatment, however, attenuated the recovery (23.08 +/- 3.04 vs. 32.28 +/- 2.37%, P < 0.05). Moreover, Se supplementation increased the sensitivity to the inotropic effect of ISO, decreased cardiac concentration of lipofuscin-like pigment and serum concentration of NO. Our results suggest that Se protects the immature heart against ischemia/reperfusion injury. It seems therefore, that ROS may affect the function of the neonatal heart, similarly as in adults.
Keywords: Rats; Perfusion; Myocardial Contraction; těhotenství; Time Factors; potravní doplňky; Rats, Wistar; Lipofuscin; Myocardial Reperfusion Injury; Myocardial Ischemia; perfuze; krysa rodu Rattus; Body Weight; selen; reperfuzní poškození myokardu; Organ Size; velikost orgánu; ženské pohlaví; zvířata; oxid dusnatý; Pregnancy; Dietary Supplements; Nitric Oxide; tělesná hmotnost; lipofuscin; časové faktory; Selenium; Heart; ischemická choroba srdeční; potkani Wistar; kontrakce myokardu; Female; srdce; Animals